IL‐10 signaling in dendritic cells is required for tolerance induction in a murine model of allergic airway inflammation. Issue 2 (3rd January 2019) - Dolch, Anja; Kunz, Stefanie; Dorn, Britta; Alessandrini, Francesca; Müller, Werner; Jack, Robert S.; Martin, Stefan F.; Roers, Axel; Jakob, Thilo
Abstract: Allergen specific tolerance induction efficiently ameliorates subsequent allergen induced inflammatory responses. The underlying regulatory mechanisms have been attributed mainly to interleukin (IL)‐10 produced by diverse hematopoietic cells, while targets of IL‐10 in allergen specific tolerance induction have not yet been well defined. Here, we investigate potential cellular targets of IL‐10 in allergen specific tolerance induction using mice with a cell type specific inactivation of the IL‐10 receptor gene. Allergic airway inflammation was effectively prevented by tolerance induction in mice with IL‐10 receptor (IL‐10R) deficiency in T or B cells. Similarly, IL‐10R on monocytes/macrophages and/or neutrophils was not required for tolerance induction. In contrast, tolerance induction was impaired in mice that lack IL‐10R on dendritic cells: those mice developed an allergic response characterized by a pronounced neutrophilic lung infiltration, which was not ameliorated by tolerogenic treatment. In conclusion, our results show that allergen specific tolerance can be effectively induced without a direct impact of IL‐10 on cells of the adaptive immune system, and highlight dendritic cells, but not macrophages nor neutrophils, as the main target of IL‐10 during tolerance induction. Abstract : IL‐10 signaling is crucial for tolerance induction in a murine model of allergic airway inflammation. Here we examined the targets of IL‐10 by using cell type specific IL‐10 receptor depleted mice. An amelioration of allergic airway inflammation after tolerance induction was observed when IL‐10R was depleted on T cells, B cells, monocytes/ macrophage, and neutrophils, but no tolerance induction could be observed in mice that lack IL‐10R on dendritic cells. These results reveal a fundamental role of IL‐10 signaling in dendritic cells during tolerance induction in allergic airway inflammation.